2004
DOI: 10.1007/s00122-003-1547-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of a novel y-type Glu-D t  1 glutenin gene of Aegilops tauschii

Abstract: A novel y-type high-molecular-weight glutenin subunit possessing a slightly faster mobility than that of subunit 1Dy12 in SDS-PAGE, designated 1Dy12.1(t) in Aegilops tauschi, was identified by one- and two-dimensional gel and capillary electrophoresis. Its coding gene at the Glu-D(t) 1 locus was amplified with allele-specific-PCR primers, and the amplified products were cloned and sequenced. The complete nucleotide sequence of 2,807 bp containing an open reading frame of 1,950 bp and 857 bp of upstream sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 42 publications
2
32
0
2
Order By: Relevance
“…The N-termini of x-type subunits are composed of 86-89 residues, while those of y-type subunits are typically 104-105 residues. The C-termini of all subunits are composed of 42 residues and the central repetitive domain comprises 630-830 residues and mainly contributes to the differences between all the subunits (Sun et al 2004;Yan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The N-termini of x-type subunits are composed of 86-89 residues, while those of y-type subunits are typically 104-105 residues. The C-termini of all subunits are composed of 42 residues and the central repetitive domain comprises 630-830 residues and mainly contributes to the differences between all the subunits (Sun et al 2004;Yan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…et Migush (GenBank: AY695379, Jiang et al 2006). However, the genes for the 1Dy subunits originating from diploid ancestors possess much higher variation in comparison to those isolated from hexaploid wheat varieties (Mackie et al 1996;Dvorak et al 1998;Gianibelli & Solomon 2003;Yan et al 2004;Fang et al 2009;Xu et al 2010). Nevertheless, wheat breeders prefer to use more-related genomes as the donors for the improvement of bread wheat.…”
mentioning
confidence: 99%
“…tauschii have been characterized (Wan et al 2005). Evidence from molecular analysis demonstrated that the HMW glutenin subunits from wheat and related species have highly conserved structures, consisting of a signal peptide (21 residues), an N-terminal domain (86-89 residues in x-type and 104 in y-type subunits), a C-terminal domain (42 residues), and a central repetitive domain (630-830 residues) that is mainly responsible for differences in molecular weight of the subunits Wan et al 2002Wan et al , 2005Yan et al 2004;Sun et al 2006;Zhang et al 2006). The HMW glutenin genes, therefore, could derive from a common ancestor.…”
mentioning
confidence: 99%